DEVELOPMENT OF HEATED STREAM ABOVE THE HORIZONTAL SURFACE - P. I. Diachek; A. E. Zakharevich; I. Yu. Hrachou (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The development of thermal contaminated air stream formed above the surface of lengthy heated plate is investigated on the basis of the mathematical model of heat and mass transfer processes. The numerical simulation results performed for the purpose of finding a way to prevent the contaminants outflow from the hood in the presence of external influence are given. Three variants of the hood side panels lengthening are considered: on either side; on the side of the fresh air supply; on the side opposite to the location of air distributors. Comparison of the effects of using these variants of hood design allowed determining that the hood panel located on the side of the coming air flow gives the greatest leakage reduction. It is found out that lengthening of the hood side panels does not ensure full localization of the contaminated convective stream.Several variants of using the screen located on the side of the lateral air flow were investigated in the course of work. Best result is observed under conditions of application of the screen symmetrically located relative to spacing between the hood and the plate. The analysis of local values of temperature and velocity fields in this case shows that losses of heated contaminated air to the workshop space are practically absent. It is found out that the convective stream can be most efficiently localized under the condition of hood-symmetric distribution of supply air. Influence of the open gate on convective stream formation in the workshop space with heat emission is considered. The shift of upward flow to the opposite side relative to the gate is observed. The radiant heat release from the board is of great importance in the temperature field formation of closely located areas of floor and walls surfaces